Pengaruh Buku Siswa IPA Terpadu Tipe Connected Bermuatan Karakter dengan Tema Fluida Darah Terhadap Hasil Belajar Siswa Kelas VIII SMP 8 Padang - Abdul Rahman Saleh Nasution; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2018)
Science lessons in junior high school are conducted in an integrated manner according to the mandate of the 2013 curriculum. Integrated IPA learning incorporates several subject from various fields of study of Physics, Biology and Chemistry. Reality at school indicatesthat the veterinary defender has not been applied optimally the IPA materials.One of the integrated science lesson students connercetd type and living being. The purpose of this research is to invertigate the effect of the book of students integrated scienceconnected type with theme of blood fluid on learning outcomes learner SMPN 8 Padang. This type research is a quasi-experimental research. The from a research design will be used is the static group comparison. Population in this research is all students of class VIII SMPN 8 Padang. Sampling in this research by purposive sampling technique.The data in this study were analyzed, aquality two everaging test and t- test then tested the determination of the influence of independent variables for both aspects of competence. The results showed that the average value of knowledge in the experimental class was 8 higher than the control class . The average results of class experimental class  were higher than control class  namely, 84,84 and 80,78.Thues the use of books of natural csience students withconnected type with the theme of blood fluid has a significant influence on the competence of knowledge and skills of grade VIII students.